2012
DOI: 10.1590/s0101-20612012005000076
|View full text |Cite
|
Sign up to set email alerts
|

Physical, chemical, technological and sensory characteristics of Frankfurter type sausage containing okara flour

Abstract: The addition of okara flour to an emulsified meat product (Frankfurter type sausage) was evaluated based on the physical, chemical, technological, and sensory characteristics of the final product. Okara, residue from soymilk production, was provided by two soymilk producing companies whose production systems were based on the hot disintegration of the decorticated (company B) or undecorticated (company A) soybeans. The okara was dehydrated using a flash dryer and then ground into flour (>420 µm). However, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
1
4
0
1
Order By: Relevance
“…In the present study, T2 improved acceptance of flavor in the sausages. Similar behavior was found by Grizotto et al (2012).…”
Section: Sensory Evaluationsupporting
confidence: 87%
“…In the present study, T2 improved acceptance of flavor in the sausages. Similar behavior was found by Grizotto et al (2012).…”
Section: Sensory Evaluationsupporting
confidence: 87%
“…Thus, all treatments were well accepted by consumers, contributing to the reduction of fat in sausages. Grizotto et al (2012) carried out a study with the addition of two types of okara flour in Frankfurter type sausages with partial (1.5%) and total (4.0%) replacement of texturized soy protein and concluded that the addition of okara flour did not influence sensory acceptance. On their research, Choe et al (2013) worked with Frankfurter sausages substituting bacon with wheat fibre in proportions of 10, 15 and 20%, and all the samples were well accepted.…”
Section: Sensory Analysismentioning
confidence: 99%
“…Several studies have shown the possibility of replacing fat with dietary fibre in meat products with good sensory acceptance (Huang et al, 2011;Grizotto et al, 2012;Schmiele et al, 2015;Talukder, 2015;Barretto et al, 2015;Borrajo et al, 2016;Carvalho et al, 2017;Bis-Souza et al, 2018;Zhao et al, 2018;Abbasi et al, 2019), increasing the intake of this component in the diet. These ingredients can contribute giving technological benefits in meat products in order to improve their nutritional and sensory characteristics (Méndez-Zamora et al, 2015;Paglarini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among the meat sausages sold in Brazil, mortadella stands out for being a fast-food item at an affordable price (Grizotto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%